Feasibility, adherence and usability of an observational digital health study built using Apple’s ResearchKit among adults aged 18–84 years - Brady, B.; Zhou, S.; Ashworth, D.; Zheng, L.; Eramudugolla, R.; Anstey, K. J. (Frontiers in Digital Health, 2025)
ObjectiveThis study evaluated the Labs Without Walls app and paired Apple Watch devices for remote research among Australian adults aged 18–84.MethodsThe study app, built using Apple's open-source ResearchKit frameworks, uses a multi-timescale measurement burst design over 8-weeks. Participants downloaded the app, completed tasks over 8 weeks, and wore Apple Watch devices. Feasibility was assessed by recruitment, remote consent, and data collection without training. Adherence was measured by task completion rates. Usability was assessed by response times, a post-study survey, and qualitative feedback.Results228 participants (mean age 53, age range 18–84; 62.7% female) were recruited nationwide, consented remotely, and provided data. 201 (88.16%) completed the 8-week protocol. Task adherence ranged from 100% to 70.61%. Health, environmental, and sleep data were collected passively. Usability feedback was excellent, with 84% rating the app as “extremely” or “a lot” user-friendly, 88% finding alert frequency “just right,” and 95.7% finding the schedule manageable. Few age or sex differences were found.ConclusionsThe Labs Without Walls app and paired Apple Watch devices are user-friendly and enable adults aged 18–84 to complete surveys, cognitive and sensory tasks, and provide passive health and environmental data. The app can be used without formal training by males and females living in Australia, including older adults. Future iterations should consider gamification and strategies to improve daily-diary survey user experience.